Green Technology Integration and Circular Economy Pathways for Sustainable Innovation - Siswadhi, Tamara Maharani; Fajrin, Noer; Jakfar; Mubarok, Ahmad; Hariri, Ahmad (Novatio : Journal of Management Technology and Innovation, 2024)
This study examines the integration of green technologies into circular economy systems as a pathway to advancing sustainable innovation. The objective was to synthesize existing literature to identify key strategies, challenges, and implications across diverse industrial and geographical contexts. A narrative review methodology was employed, drawing on peer-reviewed sources indexed in Scopus, Web of Science, and Google Scholar. The results highlight four main themes: product design and eco-innovation, renewable energy and photovoltaics, biomaterials and lignin applications, and sustainable business models. Evidence shows that lifecycle assessment tools and decision-making frameworks enhance eco-design. Advancements in solar technologies promote decarbonization but face storage and recycling challenges. Lignin valorization offers significant promise yet is constrained by technical and scalability issues. Circular business models provide systemic benefits, but their effectiveness varies depending on regulatory environments, cultural acceptance, and financial structures. The review concludes that strengthening design strategies, renewable energy deployment, biomaterial innovations, and business model adaptation are essential to overcoming systemic challenges and achieving sustainable economic transitions.